Moderating role of human capital on the relationship between social network and business performance of established manufacturing small and medium enterprises / Ehsan Fansuree Mohd Surini - Mohd Surini, Ehsan Fansuree (Institute of Graduate Studies, UiTM, 2014)
Entrepreneurs and social network theory is an emerging area despite having grabbed most attention of the researchers in last three decades. Social network is important to the entrepreneurs to gather the important resources from the alter/s. Drawing from the social network theory and resource-based view (RBV), the purpose of this study is to investigate the relationship between social network and business performance in the established manufacturing SMEs in Malaysia. The current study also will examine the moderating role of human capital on the relationship between the social network and business performance. The research data were collected through mail and self-administered questionnaire sent to owner-manager around Malaysia. A stratified random sampling was used which elicited 226 useable responses for data analysis.